Biofuels in Africa : Opportunities, Prospects, and Challenges - Mitchell, Donald (World Bank, 2012)
Biofuels offer new opportunities for African countries. They can contribute to economic growth, employment, and rural incomes. They can become an important export for some countries and provide low-cost fuel for others. There is also a potentially large demand for biofuels to meet the rapidly growing need for local fuel. Abundant natural resources and low-cost labor make producing biofuel feedstock's a viable alternative to traditional crops; and the preferential access available to most African countries to protected markets in industrial countries provides unique export opportunities. Biofuels also bring challenges and risks, including potential land-use conflicts, environmental risks, and heightened concerns about food security. This book examines the potential of African countries to produce biofuels for export or domestic consumption and looks at the policy framework needed. It is part of the effort by the World Bank's Africa region to examine critical issues that affect the region and to recommend policies that effectively address these issues while providing an enabling environment for the private sector. The book is intended to inform policy makers and the larger development community of the global and domestic market opportunities facing biofuel producers, as well as the challenges of producing biofuels, in the Africa region.